METODE DAN MATERI DAKWAH UNTUK WANITA BERMASALAH - Baroroh, Umul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2018)
Today, along with the pace of information growth, technology raises increasingly complex social problems. The complexity of the problems faced by humans increases and cones like a mountain. For those who are able to overcome social problems will not create new problems. Conversely, for people who are not able to adapt to the development of the times will have new problems. In today's modern era many women have problems that make it one of the